Model Pemahaman Front Pembela Islam (FPI) Terhadap Al-Qur’an Dan Hadis - Abdul Hakim Wahid (Refleksi: Jurnal Kajian Agama dan Filsafat, 2018)
The Islamic Defenders Front (FPI) is very famous for the amar ma'ruf and nahi mungkar movement, and launched the national anti-immoral movement. However their movement always seems to use violence, so there is a presumption that FPI's religious pattern shows the influence of petro Islam that rigidly and textually-dominated with a harsh understanding to the practice of violation on religious values. With the semantic approach to the Habib Riziq’s book entitled Dialog FPI-Amar Ma'ruf Nahi Munkar, this paper prove that the FPI's interpretation to the Qur'an and hadiths which is the reference of their every action, has used a contextual approach, but seems that their understanding is less comprehensive.